Effectiveness and Efficiency Of Baznas With ACR and ISZM Method - Dina, Mushlihatud; Tista Putriana, Vima (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to compare the analysis of effectiveness and efficiency of BAZNAS Solok Regency and BAZNAS Solok City for the period 2018 - 2021 using the Allocation to Collection Ratio (ACR) and the International Standard of Zakat Management (ISZM) method. The analysis technique is carried out using ACR ratio analysis which consists of Gross Allocation to Collection Ratio, Gross Allocation to Collection Ratio Non-Amil, Net Allocation Ratio, and Net Allocation Ratio Non-Amil while ISZM ratio consists of program expense ratio, operational expense ratio, collection expense ratio, and collection efficiency. The result found that (1) Both BAZNAS received an effective title in calculating effectiveness using four ratios through the ACR method. However BAZNAS Solok Regency is better than BAZNAS Solok City for effectiveness because it has obtained a score of 100% for four consecutive years for the calculation of Net Allocation to Collection Ratio and Net Allocation to Collection Ratio Non Amil (2) For the efficiency ratio BAZNAS Solok Regency and BAZNAS Solok City received the efficient title for the program expense ratio, collection expense ratio and collection efficiency, but it was not efficient for the operational expense ratio because it obtained a value of more than 12.5%.